The Impact of Credit on Multidimensional Poverty in Rural Areas: A Case Study of the Indonesian Agricultural Sector - Tegar Rismanuar Nuryitmawan (Universitas Muhammadiyah Malang, 2021)
Poor farmer households are a vulnerable group in rural areas. Various poverty alleviation measures have been launched to help poor farmer groups become more prosperous. The policies launched were in the form of cash transfers, empowerment, and access to formal financial institutions. Policies for providing formal financial access continue to face many obstacles, one of which is credit risk and farmer literacy. The study aims to estimate the impact of credit on multidimensional poverty in poor farmer households in Indonesia. Secondary data were obtained from the Indonesian Family Life Survey (IFLS) batch 4 and 5. The impact estimation method used was propensity score matching combined with the difference in differences. The results showed that credit programs for poor farmers, initiated by official financial institutions, significantly helped farmers out of poverty, although the value was small. The addition of control variables such as education, ownership of household assets, and ownership of agricultural land actually made the credit program more modifiable at the policy level. Credit can be used as a complement to policies related to improving farmer education and knowledge in the form of agricultural modernization, as well as to scale-up of farmer household businesses.